2017
DOI: 10.3390/ijerph14070770
|View full text |Cite
|
Sign up to set email alerts
|

Synchronization of Human Autonomic Nervous System Rhythms with Geomagnetic Activity in Human Subjects

Abstract: A coupling between geomagnetic activity and the human nervous system’s function was identified by virtue of continuous monitoring of heart rate variability (HRV) and the time-varying geomagnetic field over a 31-day period in a group of 10 individuals who went about their normal day-to-day lives. A time series correlation analysis identified a response of the group’s autonomic nervous systems to various dynamic changes in the solar, cosmic ray, and ambient magnetic field. Correlation coefficients and p values w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
64
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 96 publications
(89 citation statements)
references
References 63 publications
5
64
0
2
Order By: Relevance
“…We collected 720-hour HRV data from 19 participants and obtained geomagnetic and solar activity. Previous studies found significant, strong correlations between HRV and geomagnetic activity 8,9 In seeming agreement with this previous work, we also found significant correlations between the two type of variables before correction for the autocorrelation inherent to time-series. After correction for autocorrelation, however, we only found a significant correlation between very low-frequency power of HRV and K index and a significant anticipatory effect on heart rate with Ap index.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…We collected 720-hour HRV data from 19 participants and obtained geomagnetic and solar activity. Previous studies found significant, strong correlations between HRV and geomagnetic activity 8,9 In seeming agreement with this previous work, we also found significant correlations between the two type of variables before correction for the autocorrelation inherent to time-series. After correction for autocorrelation, however, we only found a significant correlation between very low-frequency power of HRV and K index and a significant anticipatory effect on heart rate with Ap index.…”
Section: Discussionsupporting
confidence: 92%
“…Inspired by previous findings of time-dependent effects of geomagnetic activity on HRV 8,12 , we also examined potential relationships with an offset of one day in both anticipatory or consequential manners. As a result, we found a significant relationship of an anticipatory effect such that heart rate was lower the day before higher geomagnetic activity, though the correlation was weak (r=-.09).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations